SAT0412 Tuberculosis reactivation during biological therapy. (12th June 2018) - Carlan, R.; Simon, S.P.; Muntean, L.; Tamas, M.M.; Damian, L.; Felea, I.; Filipescu, I.; Rednic, S.
Abstract : Background: With the increasing use and wide variety of biological therapies, there is a concomitant increase in concern for associated opportunistic infections, especially for Mycobacterium tuberculosis. ¹ Objectives: The aim of this study was to identify patients who have developed tuberculosis (TB) reactivation during treatment with a biological agent. Methods: We included patients treated with biological agents in a tertiary Department of Rheumatology who had developed TB and were registered in the national registry for biological therapy. Demographic (urban or rural environment), clinical, therapeutic (biologic agent used) and comorbidities data were retrieved from the database. Results: The database included 505 patients: 314 patients with rheumatoid arthritis (RA), 129 patients with ankylosing spondylitis (SA) and 62 patients with psoriatic arthritis (PsA). Prior to the start of biological therapy, tuberculosis screening for latent infection was conducted in all patients. Eight patients (1, 58%) were identified as being diagnosed with TB reactivation during biological therapy: 5 RA and 3 SA patients Two had positive tuberculin test (TST) at baseline and required chemoprevention therapy prior to the initiation of the biological agent (respecting the preexisting guidelines). Demographic data shows 62.5% patients from urban areas, 50% female and 50% male. Regarding comorbidities, one patient had biapical pachypleuritis (probably TB sequelae), antiphospholipid syndrome and pulmonary hypertension; one had chronic kidney failure and inflammatory bowel disease. The other six patients had minor comorbidities. 62, 5% of patients were treated with oral corticosteroids combined with DMARDs. Four patients have been treated with infliximab, three with adalimumab and one with etanercept. The average time to TB reactivation was 19.6 months (range 2 months to 52 months). Patients who had TB reactivation after two months of biologic therapy were treated with infliximab. Four patients had developed pulmonary TB; one case was described as a miliary complicated with bacillary peritonitis (peritoneal biopsy). One patient had developed lymph node TB (lymph node biopsy) and one TB of the wrist (switch therapy was not chosen yet). One particular case was of a patient that had developed TB meningitis with lymphadenitis and a compressible tuberculoma with spastic paraparesis. Switching of biological agent was chosen in 5 patients without another reactivation of tuberculosis. The biological agents chosen in 40% was rituximab, 20% was etanercept, 20% was adalimumab and 20% was infliximab. Conclusions: Pulmonary and extrapulmonary TB reactivation equally occurred during anti TNF therapy. In some cases, reactivation of tuberculosis occurred even with chemoprevention. Reference: [1] Juliana Lopesa, Ana Machadoa, Sara Martinsa, Sara Piresa, Catarina Brancoa, Joana Fragosob, Diogo Guerrab, Patricia Camposc, Mariana Brandaoa, Graziela Carvalheirasc, Teresa Mendonca -The Challenge of Tuberculosis Infection Related to Adalimumab: A Subtle and Rare Presentation. J Med Cases2018;9(1):23–25. Disclosure of Interest: None declared